2013
DOI: 10.1021/es3040472
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Toxic Mixtures of Non-Toxic Chemicals: “Solubility Addition” Increases Exposure for Solid Hydrophobic Chemicals

Abstract: This study addresses the question whether hydrophobic organic chemicals exerting no toxicity at their solubility limit (saturation) can form a toxic mixture. Spiking methods generally do not allow testing exactly at saturation without introducing microcrystals. Passive dosing was thus applied to test the acute toxicity of several high melting point PAHs and their mixtures at the respective saturation levels to aquatic and terrestrial invertebrates. With the aquatic Daphnia magna, anthracene, chrysene, and benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
6
65
1
Order By: Relevance
“…Although potentiation effects are considered when evaluating risk in specific cases, such as in workplace exposure or for pesticide residues in food and feed (Smith et al, 2013), most regulatory frameworks for chemicals continue to focus on the testing of single substances. However, here we demonstrate that the combined toxicity of several substances-a realistic scenario-can differ greatly from that produced by each individual substance alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although potentiation effects are considered when evaluating risk in specific cases, such as in workplace exposure or for pesticide residues in food and feed (Smith et al, 2013), most regulatory frameworks for chemicals continue to focus on the testing of single substances. However, here we demonstrate that the combined toxicity of several substances-a realistic scenario-can differ greatly from that produced by each individual substance alone.…”
Section: Resultsmentioning
confidence: 99%
“…Here we found that the combination of two distinct NPs at concentrations causing no or very limited cytotoxic effects when present alone led to a strong enhancement of toxicity. Potentiation phenomena have been described for a variety of chemicals in a number of systems (for instance studies of Smith et al (2013) in D. magna and Torre- Roche et al (2013) in C. pepo and G. max). However, few data are available on such effects after exposure to a mixture of NPs (Chen et al, 2008;Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the toxicity of single chemicals can be modified when present in a mixture through toxicokinetic interactions with cosolutes, solubility addition (Smith et al, 2013b) or a joint action at the target site, which can enhance or inhibit the effect of endogenous hormones (Carpenter et al, 2002;Silva et al, 2002). It has also been shown that minor changes in mixture composition can cause larger shifts of endocrine responses (Kortenkamp, 2007).…”
Section: Mixture Toxicitymentioning
confidence: 99%
“…The median value of chemical activity associated with acute baseline narcosis in fish is quite similar to previously reported values using other datasets. Median lethal activity values of 0.037 for fish and 0.19 for rodents have been calculated [8,9] and 0.02 to 0.05 for aquatic invertebrates have been measured [16].…”
Section: Thermodynamic Partitioningmentioning
confidence: 99%